The Formation of the Talmud Scholarship and Politics in Yitzhak Isaac Halevy's Dorot Harishonim - Bergmann, Ari (Perspectives on Jewish Texts and Contexts, 2021)
This book examines the talmudic writings, politics, and ideology of Y.I. Halevy (1847-1914), one of the most influential representatives of the pre-war Eastern European Orthodox Jewish community. It analyzes Halevy's historical model of the formation of the Babylonian Talmud, which, he argued, was edited by an academy of rabbis. That model also served as a blueprint for the rabbinic council of Agudath Israel, the political movement he founded.